Transnational Lithuanianness: Identity and Heritage in Diaspora - Čiubrinskas, Vytis (Sociologija. Mintis ir veiksmas, 2005)
The aim of the article is to delineate contours of certain social strategies, images and discourses as well as cultural practices related to the Lithuanianness, as culture and heritage imagined, constructed and contested in and among different waves and generations of the Lithuanian Americans. The period, the wave of immigration, the way it happened and in particular the rooted-ness in the American soil are basic markers for a distinct pattern of Lithuanianness to be recognized. Any one of these patterns falls into the ascription of a certain social strategy, ideology and politics of identity and is motivated and re-enforced by ‘symbolic capital’ taken from ‘repository’ (Castells 1997) of national or ethnic heritage. Consequently, the Lithuanian heritage gains its meaning as well as any item of the national ‘repository’ becomes imagined, (re) constructed and circulated differently among at least four generations of the Lithuanian descendants, who started to settle in the United States in 1860’s as economic immigrants, continued in the late 1940s as political DPs (who have moved from displaced person’s camps in Germany) and do continue up to the recent wave of post-Soviet Lithuanian immigration. Lithuanianness as ethnicity can operate as shelter and aid. This is a strategy of particular importance for the each category of the Lithuanian immigrants. It is a sort of model for ethnic subsistence, based on neighborhood ties, as well as on shared language skills and also on an appreciation of common cultural heritage in terms of ethnic foods and customs. Ethnic emancipation is a strategy especially evident during the establishment of the ethnic Lithuanian Catholic Church with service in Lithuanian although all believers in the diaspora never supported such a strategy. Nationalist mission is a strategy of cherishing, perpetuating and retaining ethnicity/nation-ness in terms of culture, language, traditions and heritage. The Lithuanian Charter of 1949 is the best example of the nationalist imperative and mission, applicable to any Lithuanian in exile “to pass on the culture to future generations to insure the eternal nature of his nationality’ The parish of the Lithuanian Catholic Church is the most visible social network in the case of ethnicity. The role of the parish to shelter and embrace ethnic life, is most visible through the whole history of the Lithuanian diaspora in the US, in particular in its early stages. Only one other ethnic organization – the Lithuanian Community, (Lietuviu bendruomene) founded and maintained almost entirely by DPs, primarily for nationalist activities, could be compared in scale and popularity with the parish. For many that immigrated after World War II, the Lithuanian Community was at least of equal importance as was the parish to old-timers. The social networks of the post-communist immigrants are based on common social and economic experience of the Communist regimes, visible in the job market, such as the economy of favors, nepotism and clientalism. Participation in such social networks ‘of their own’ or ‘groups of friends’ is a source of higher salaries, more secure jobs, benefits, and finally, means of successful adaptation, helping immigrants to achieve higher social and economic mobility in American society. Earlier generations of immigrants also transplanted their social experiences from the home country, but unlike new immigrants, they were met by, and exposed to, the same or, at least, very similar social bonds in the new country, where the parish stands as the best example. The most critical issue along all waves of immigration is a normative image of home country. Old-timer’s wave of immigration is overwhelmingly guided by rural and heroic romanticism of the old underdeveloped country. Their image of the people of this country is that of a ‘strong’ people who founded a medieval empire, the Grand Duchy of Lithuania and regained independence from Russia twice during the last century, in 1918 and in 1990. It is also the main source of being ‘proud of being Lithuanian’. The DPs image of the home country was constructed from the typical political refuge experience. The occupied and suffering country, left behind at the end of the World War II, encouraged them to take on a mission of regaining nation and retaining its culture. For the post-Communist newcomers, the image of the home country is full of postcolonial transitional uncertainty, with a clear understanding that Lithuania belongs to the Eastern European region with Russian as lingua franca. They are very self-conscious, and their image of the home country and Lithuanian people is in many ways focussed on the ‘unique-communist regime – experience’ as possessed by the immigrants themselves and their compatriots in Lithuania. The question of sociocultural production of meaning of ethnicity implies praxis of everyday life in diasporas, where manipulation of the Lithuanianness takes place. At least two Lithuanian cultural and heritage practices could be defined. The first involves the essentialisation and codification of culture and heritage. Discourses on the issue of ‘birthright to glorious Lithuanian heritage’ already appeared in the Lithuanian newspapers published in the US at the end of the nineteenth century. The issue of the Lithuanian culture was altered significantly by DPs. The perpetuation of the notion of occupied, and thus repressed and deprived, Lithuanian nation and its culture gained political acceptance within the US government. It gave political motivation for Lithuanian culture in the US to become more than one of many ethnicity cultures within the ‘American dream’, and to acquire a ‘public’ and ‘prestigious’ image. So, despite the predominant ‘Melting Pot’ cultural politics of the US during the post World War II period, the Lithuanian label held moral and cultural prestige. A second visible Lithuanian cultural and heritage practice in America invokes a cultural bricolage of retained and adopted elements. Cultural bricolage is conducted by creating new meanings for national/ethnic cultural forms of kinship, language, artifacts, visual-virtual materials, narratives and stereotypes. Ethnic identifications phrased as “Proud to be Lithuanian” or ‘I am American first and Lithuanian always’ along with a few catchwords or phrases in Lithuanian are starting point in practicing cultural bricoleur. An interest in family genealogies, which is usually strongly related to an interest in finding ethnic roots and eventually ends up in ethnic pilgrimages to Lithuania as a homeland (or the land of ancestors), also belongs to that practice. Material objects, which are supposed to belong to the ethnic/national repository, are used for decoration of private homes and public halls, usually enshrined by ethnic shrines.
Keywords: ethnicity; identity; heritage; transnational Lithuanianness